Improving Students’ English Vocabulary Mastery Using Sentence Completion in Descriptive Text (ELang | An English Language Education Journal, 2018)
This paper entitled Improving Students’ English Vocabulary Mastery using Sentence Completion in Descriptive Text. This papers purpose is to observe how the students improve their English vocabulary mastery using sentence completion, especially in descriptive text. The writer used quasi-experimental design, which consists of two groups, those are: experimental group and control group. It also investigated by using pretest, treatment and post-test. The writer chose SMP KP 1 Baleendah in the second grade as the population of research, which is consist of 306 students in 2017/2018 academic year. The writer took 25 students as the sample of research. The writer gave t-test to the students and got the analysis result of the t-observe is 0.149. The instruments were tests and they were analyzing by statistical formula. The value of t-table was gained from the degree of freedom (df) from two groups, each group consists of 25+25-2 = 48, at the level of significant 0.05 for two tailed t-test was 2.000. Based on the result of t-test, the writer can observe that t-observe is lower than t-table. After the writer gave treatment using sentence completion to the students, the computation result of post-test in the t-observe was 3.085. The writer compared the two values of t-observe (to) was bigger than that the critical t (t-table) it is 3.085 > 2.000. So, the Null Hypothesis (Ho) was rejected, and the Alternative Hypothesis (Ha) was accepted. It means that sentence completion in descriptive text is effective to improve students’ English vocabulary mastery. And it also means that sentence completion in descriptive text significantly more effective to improve students’ English vocabulary mastery of the second grade of SMP KP 1 Baleendah than conventional method. The writer has shown the result of this paper and hopes this technique will give the contribution on learning and teaching English vocabulary in the classroom. The writer also hopes that the English teacher will motivate the students to learn more about English vocabulary, which can make the students easily learn English.